Assessment of Partial Edentulism Based on Kennedy’s Class III Classification - Palak Mayur Shah1 , Revathi Duraisamy2 , Manjari Chaudhary (Indian Journal of Forensic Medicine & Toxicology, 2020)
Edentoulousness falls in a different category among the various conditions of dental origin. A partiallyedentulous arches classification helps to identify the possible combinations of teeth to edentulous ridges, thusfacilitating discussion and communication among dental professionals. Kennedy’s classification providesimmediate visualisation and assessment of design features of removable partial dentures. The aim of thestudy was to assess the prevalence of partial edentulism based on Kennedy’s class III situation in the upperarch among the patients visiting a private dental hospital. This retrospective study included 10,327 subjectswho reported during June 2019 to March 2020. The sample size was collected and retrieved from the onlinedatabase. Tabulation of data was done followed by statistical analysis. Out of the 10,327 subjects reported tothe dental hospital, 6453 subjects were diagnosed with Kennedy’s class III (62.4%). It was most commonlyseen in age groups of 50-59 years (26.7%), and in males (54%). There was a significant association betweengender and Kennedy’s class III (p=0.000) and age and Kennedy’s class III (p=0.000) Within the limits of thestudy, it was found that there was a significant relationship between gender and Kennedy’s class III and ageand Kennedy’s class III.